Informe sobre las estrategias tomadas para medir la influencia del crédito en la rentabilidad de las Mypes de cartera asignada - Quezada Llaury, Fabio Raúl (2019)
The objective of this Report is to obtain the Professional Degree of Economist, which has been prepared according to the Regulations of Degrees and Degrees of the Faculty of Economic Sciences of the National University of Trujillo. The report describes the professional experience that occurred during the tenth cycle of the economics degree, first as a practitioner and then at a professional level, this process occurred as I assumed greater responsibilities in the labor field with a series of tools that They configured my professional profile as knowledge, skills, academic training and acquired work experience. In these 10 years that I have been practicing the profession, I have been able to translate into my daily work all the knowledge learned in the classrooms of the university. I have mainly developed the facet of Business Advisor in various organizations, such as Rural box Savings y Credits Our People, Savings Bank and Credits Trujillo and lately working in Mybank - Bank of the Microenterprise; companies dedicated to the Business Banking activity of micro, small and medium enterprises framed within the scope of the General Law of the Financial System and Insurance. Companies grow and develop thanks to the quality of the staff that works in it and the support and support they receive from decision makers, so in the Professional Sufficiency Work the external and internal conditions are exposed in which it develops and relating the knowledge acquired in the university classrooms and the practical performance in the workplace.